ANALYZING THE STORE ATMOSPHERE OF CENTRO DEPARTMENT STORE IN MANADO TOWN SQUARE USING IMPORTANCE - PERFORMANCE ANALYSIS (IPA) - Manuahe, Felicia; Lapian, S.L.H.V.Joyce; Tumbuan, Willem A (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: The competition of retail stores in Indonesia requires the company to survive and compete in this business market. One of the strategies that can be undertaken by the company is to build a good store atmosphere of the store. The aim of this research is to analyzing the store atmosphere of Centro department store in Manado measured by cleanliness, music, scent, temperature, lighting, color, and display/layout. This research is quantitative type of research and use primary data obtained through questionnaire from 100 respondents as customers who have visited Centro Department Store more than twice, the sampling method is convenience sampling, and Importance â€“ Performance Analysis as a measurement tool. The result of this research found display/layout is located in quadrant I, cleanliness, temperature, and lighting are located in quadrant II, music, scent, and color are located in quadrant III. Based on the result of this research, Centro Department Store to pay more attention for its store atmosphere aspect as it has an influence to the customer. A store atmosphere performance could lead to customer attraction and increasing sales.Â Keywords: store atmosphere importance and performance analysis, centro department store